2002
DOI: 10.1115/1.1485294
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives in Modeling Film Cooling of Turbine Blades by Transcending Conventional Two-Equation Turbulence Models

Abstract: The paper presents recent trends in modeling jets in crossflow with relevance to film cooling of turbine blades. The aim is to compare two classes of turbulence models with respect to their predictive performance in reproducing near-wall flow physics and heat transfer. The study focuses on anisotropic eddy-viscosity/diffusivity models and explicit algebraic stress models, up to cubic fragments of strain and vorticity tensors. The first class of models are direct numerical simulation (DNS) based two-layer appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 28 publications
(26 reference statements)
3
29
0
3
Order By: Relevance
“…Azzi and Lakehal [14] studied two classes of turbulence models, namely anisotropic eddy-viscosity/diffusivity and explicit algebraic stress models in modeling film cooling of turbine blades. They investigated the predictive performance of the turbulence models in reproducing near-wall flow physics and heat transfer on a flat plate by a row of streamwise injected jets for a density ratio of 2.0.…”
Section: Introductionmentioning
confidence: 99%
“…Azzi and Lakehal [14] studied two classes of turbulence models, namely anisotropic eddy-viscosity/diffusivity and explicit algebraic stress models in modeling film cooling of turbine blades. They investigated the predictive performance of the turbulence models in reproducing near-wall flow physics and heat transfer on a flat plate by a row of streamwise injected jets for a density ratio of 2.0.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental researches and DNS (Direct Numerical Simulation) results revealed that in the vicinity of walls, the turbulent fluctuation w w   in flow direction is generally larger than the normal turbulent fluctuation u u   . However, the traditional eddy-viscosity turbulence model with the Boussinesq approximation could not catch this feature, which can be proved by Azzi and Lakehal [12]. So in the present study, w w   / u u   is calculated by the correlation fitted by experimental data [13].…”
Section: Turbulence Modelmentioning
confidence: 95%
“…In another study by Azzi and Lakehal (2001), two classes of k-e model and Reynolds stress transport model were used to simulate both a flat plate and a symmetrical turbine blade. In the first case, a two-layer approach was used where a DNS-based one-equation model was applied in the viscous region and k-e model was applied in the outer region.…”
Section: Introductionmentioning
confidence: 99%